A participatory evaluation of the health promotion programme “more healthy years of life” programme among senior citizens in Sweden - Ann Johansson; Irene Ericsson; Martina Boström; Anita Björklund; Sofi Fristedt (Cogent Medicine, 2018)
Background: Older adults have, in general, been sparsely involved in development and evaluation of programmes intended to promote their health. Aim: To describe older adults’ reflections on and involvement in the development and evaluation of a health promotion programme. Material and Method: Ten older persons participated in a health promotion programme (HPP) focusing on activity during four sessions. After each HPP session, focus group discussions were held, analysed through qualitative content analysis. Results: The main theme; “Being involved adds value and new experiences to life“, were built from sub-themes; “From sceptical individual to engaged group member”, “From beholder to active co-creator”, and “From individual knowledge recipient to collective knowledge sharer”. Conclusions: Having a leader with a gerontological competence was mentioned as important, as well as to integrate existential topics into the HPP. Social inclusion together with the possibility to influence the HPP had a positive effect on the participants and provided a sense of belonging. Significance: Several contributions to the development of the HPP were given, that would not have been captured without the reflections and involvement of the participants. However, more and larger studies are needed to develop strategies that enable older adult’s involvement in the development of HHP.